2017
DOI: 10.1038/onc.2017.253
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein D inhibits activation of non-small cell lung cancer-associated mutant EGFR and affects clinical outcomes of patients

Abstract: Tyrosine kinase inhibitor (TKI)-sensitive and TKI-resistant mutations of epidermal growth factor receptor (EGFR) are associated with lung adenocarcinoma. EGFR mutants were previously shown to exhibit ligand-independent activation. We have previously demonstrated that pulmonary surfactant protein D (SP-D, SFTPD) suppressed wild-type EGFR signaling by blocking ligand binding to EGFR. We herein demonstrate that SFTPD downregulates ligand-independent signaling in cells harboring EGFR mutations such as TKI-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…For instance, Hasegawa et al [13] demonstrated that SFTPD suppressed the proliferation, migration and invasion of A549 cells by inhibiting the epidermal growth factor signaling. Umeda et al [15] reported that high serum SFTPD levels were associated with a lower number of distant metastases and better prognosis. Besides, recent studies also suggested that SFTPD could suppress the progression of pancreatic cancer by inducing epithelial-mesenchymal-transition (EMT) and apoptosis of pancreatic cancer cells [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Hasegawa et al [13] demonstrated that SFTPD suppressed the proliferation, migration and invasion of A549 cells by inhibiting the epidermal growth factor signaling. Umeda et al [15] reported that high serum SFTPD levels were associated with a lower number of distant metastases and better prognosis. Besides, recent studies also suggested that SFTPD could suppress the progression of pancreatic cancer by inducing epithelial-mesenchymal-transition (EMT) and apoptosis of pancreatic cancer cells [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, SFTPB and SFTPC are hydrophobic proteins with the capacity of mitigating surface tension in the lung [12]. Strikingly, it has been proposed that SFTPD expression was associated with tumour progression and survival of patients with lung cancer [13][14][15]. Furthermore, recent evidence also showed that SFTPD could suppress the progression of pancreatic cancer by inducing epithelial-mesenchymal-transition (EMT) and apoptosis of pancreatic cancer cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that SP-A down-regulates EGFR by mechanisms differing from those of SP-D. Our study indicated that through the interaction between CRD of SP-D and N-glycans of EGFR, SP-D suppresses EGF signaling by interfering with ligand binding to EGFR, EGFR dimerization, or EGFR autophosphorylation (11,26). In contrast, lectin activity of SP-A and N-glycans of EGFR were not involved in the interaction between SP-A and EGFR.…”
Section: Sp-a Down-regulates Egf Signalingmentioning
confidence: 69%
“…The SP-A concentrations used in this study are within the best estimates of the physiological ranges of the lung tissue. EGFR is expressed in the basolateral surface of the epithelial cells (26), whereas SP-A is secreted into the alveolar space. Therefore, we infer that a small amount of SP-A in serum or interstitial tissues might weakly regulate EGF signaling in normal alveolar epithelial cells.…”
Section: Sp-a Down-regulates Egf Signalingmentioning
confidence: 99%
“…Pulmonary surfactants are composed of four proteins (SFTPA1, SFTPB, SFTPC, and SFTPD) that are produced by type II alveolar epithelial cells such as A549 [6]. Surfactant proteins are reported to be involved in the regulation of the immune system, and in enhancing the absorption of surfactant phospholipids into the air-liquid interface and reducing the surface tension within the lungs [7,8]. Pulmonary surfactant level is widely used as a biomarker of lung cancer [9].…”
Section: Introductionmentioning
confidence: 99%